Pengaruh Jumlah Pengunjung Daya Tarik Wisata (DTW) Terhadap Occupancy Hotel Dengan Moderating Variabel Jumlah Kamar Tersedia Di Daerah Istimewa Yogyakarta - Atun Yulianto (STIE Pariwisata API Yogyakarta, 2019)
Effect Of The Number Of Visitors Attraction At The Occupancy Hotel With Moderating Variables Of Rooms Are Available In Daerah Istimewa Yogyakarta. Daerah Istimewa Yogyakarta as a tourist city saves the potential of tourist visits which strongly supports the growth of the hospitality industry. With the potential of foreign and international tourist markets visiting existing tourist attractions, at least become a potential market niche in the hotel industry in the morning to increase occupancy hotels. Hotel expectations of tourist arrivals increase the optimism of hotel management that room occupancy rates will be met according to the planned budget. However, it needs to be measured how much the influence of foreign tourists and the archipelago on occupancy hotels, so the hotel management is not wrong in its planning. The research method used is quantitative descriptive with regression analysis. The results of this study indicate that there is no significant direct influence from foreign tourists on room occupancy rates, while domestic tourists have a significant direct influence on room occupancy rates. With moderating variables the number of rooms available, hence there is an increase in indirect influence of foreign and domestic tourists on the occupancy rate of hotel rooms in Daerah Istimewa Yogyakarta.